METAPHORICAL LANGUAGE IN “THE LORD OF THE RINGS AND THE FELLOWSHIP OF THE RINGS” MOVIE (A CONVERSATION ANALYSIS) - La Dunifa; La Ode Mutawakal (English Education Department, 2022)
This study aimed to analyze the metaphors in the film “The Lord of The Rings and The Fellowship of The Rings” (LR & FR) and explained the metaphors structurally, orientationally, and ontologically. The problem studied in this paper is